Encyclopedia of forensic and legal medicine - Payne-James, Jason; Byard, Roger W. (Elsevier, 2015)
Encyclopedia of Forensic and Legal Medicine, Volumes 1-4, Second Edition is a pioneering four volume encyclopedia compiled by an international team of forensic specialists who explore the relationship between law, medicine, and science in the study of forensics. This important work includes over three hundred state-of-the-art chapters, with articles covering crime-solving techniques such as autopsies, ballistics, fingerprinting, hair and fiber analysis, and the sophisticated procedures associated with terrorism investigations, forensic chemistry, DNA, and immunoassays. Available online, and in four printed volumes, the encyclopedia is an essential reference for any practitioner in a forensic, medical, healthcare, legal, judicial, or investigative field looking for easily accessible and authoritative overviews on a wide range of topics. Chapters have been arranged in alphabetical order, and are written in a clear-and-concise manner, with definitions provided in the case of obscure terms and information supplemented with pictures, tables, and diagrams. Each topic includes cross-referencing to related articles and case studies where further explanation is required, along with references to external sources for further reading.